Reestructuración comercial y administrativa en la empresa Pastelería AMDRED (2019)
The Degree Work developed below, is based on the commercial and administrative restructuring of the AMDRED Pastry Shop, which is a company dedicated to the production and commercialization of bakery products made with flour located in the city of Bogotá D.C. (Colombia). For their development, they use both primary and secondary sources of information that provide content related to the sector, sub-sector and other interests that are important for the preparation of this, they use tools that support the development of the proposals and suggestions made by offering an analysis which supports the project.